Examining Indonesia's Behaviour Patterns in the EU's Request for a Ban onIndonesia's Nickel Exports at the World Trade Organisation (WTO) - Cania, Maharani; Asmana; Muthiah Rahmi; Zaky Al-Hasbi (JLAST : Journal of Law and Social Transformation, 2024)
Indonesia is one of the largest nickel ore producers in the world. However, as a nickel oreexporter, Indonesia has not seen any benefits from this activity. The nickel ore export banpolicy issued by Indonesia was then sued by the European Union through the WTO whichended in Indonesia's defeat. Nevertheless, Indonesia continues to ban nickel ore exportsbecause it considers the WTO decision not final. After all, an appeal has not been made. Thisresearch was conducted with a descriptive qualitative method using secondary data in theform of data that had been found and released first by previous researchers. This researchaims to see how Indonesia's attitude towards the WTO ruling.